The challenges of planning and designing urban green networks in Scandinavian and Chinese cities. Issue 3 (2nd July 2016) - Xiu, Na; Ignatieva, Maria; Konijnendijk van den Bosch, Cecil
Abstract: During the 20th century, a variety of concepts were developed aimed to provide frameworks for green space planning and design in urban areas. Both China and Scandinavia represent important experience in green space planning and management. However, none of the current concepts is generated based on the explicit combination of both a Western and Eastern context. In this paper, based on the analysis of various green space planning concepts and their development, a novel "hybrid' approach is introduced. This "Green Network' concept focuses on green and blue connectivity in urban areas and comprises the network of green spaces and the surface water system within and around settlements. The concept offers a platform for integrating best practices from Scandinavian and Chinese open space planning and can provide a guiding tool for sustainable urban development.